2021
DOI: 10.1158/2767-9764.crc-21-0076
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Modulation of Ibrutinib Pharmacokinetics through CYP3A Inhibition

Abstract: Ibrutinib (Imbruvica; PCI-32765) is an orally administered inhibitor of Bruton's tyrosine kinase that has transformed the treatment of B-cell malignancies. However, ibrutinib has very low oral bioavailability that contributes to significant variability in systemic exposure between patients, and this has the potential to affect both efficacy and toxicity. We hypothesized that the oral bioavailability of ibrutinib is limited by CYP3A isoform–mediated metabolism, and that this pathway can be inhibited to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…However, using the 140‐mg dose of ibrutinib with posaconazole, as recommended in the European prescribing information, will lead to exposures that markedly exceed those with standard daily doses in most individuals, likely leading to risk of concentration‐dependent adverse effects. Similar to the above suggestions, both the average change in bioavailability or AUC and reduction in interindividual variability should be taken into account if CYP3A inhibitor drug‐drug interactions are intentionally used to boost ibrutinib pharmacokinetics, as suggested previously 11,32–34 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, using the 140‐mg dose of ibrutinib with posaconazole, as recommended in the European prescribing information, will lead to exposures that markedly exceed those with standard daily doses in most individuals, likely leading to risk of concentration‐dependent adverse effects. Similar to the above suggestions, both the average change in bioavailability or AUC and reduction in interindividual variability should be taken into account if CYP3A inhibitor drug‐drug interactions are intentionally used to boost ibrutinib pharmacokinetics, as suggested previously 11,32–34 …”
Section: Discussionmentioning
confidence: 92%
“…Similar to the above suggestions, both the average change in bioavailability or AUC and reduction in interindividual variability should be taken into account if CYP3A inhibitor drug-drug interactions are intentionally used to boost ibrutinib pharmacokinetics, as suggested previously. 11,[32][33][34] It has been suggested that CYP3A4 inhibitors can be intentionally used together with ibrutinib to reduce its cost. 11,34,35 The financial burden of standard-dose ibrutinib treatment is extensive.…”
Section: Evaluation Of Clinically Recommended Dose Adjustments Of Ibr...mentioning
confidence: 99%
“…Since dofetilide is at least partially metabolized by CYP3A4, it has been suggested that concurrent administration of dofetilide with inhibitors of this enzyme could potentially result in an increase in the plasma concentrations of Dofetilide [ 24 , 49 , 50 ]. To explore the likelihood of this interaction mechanism, we next performed pharmacokinetic studies with dofetilide in mice lacking all CYP3A isoforms (CYP3A −/− mice) [ 51 ]. These studies revealed that the deficiency of CYP3A did not significantly influence the concentrations of dofetilide in plasma ( Figure 5 A,B,D,G) or urine ( Figure 5 C) after oral or i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Microsomal Experiments. The liver metabolism of vincristine was conducted in vitro using mouse and human liver microsomes as previously described (Eisenmann et al, 2021). All assays were conducted in a total volume of 100 μL.…”
Section: Chemicals Andmentioning
confidence: 99%